Notes on the hypersonic boundary layer transition - Wenkai Zhu (Advances in Aerodynamics, 2022)
Abstract A brief discussion is given in this note to clarify the transition path of the hypersonic boundary layer. The first mode plays an important role in the hypersonic boundary layer transition and should not be ignored. The second mode may enhance the boundary layer transition, but it is not the decisive factor affecting the transition.